Contextual Fiqh Paradigm in Determining the DSN-MUI Fatwa on Non-Cash Gold Purchase and Sale (Abdullah Saeed's Ethico-Legal Value Hierarchy Approach) - Achmad Nursobah; Abu Hapsin; Mahsun; Muhajir (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This article examines the use of a hermeneutical approach in the process of istinbat (legal reasoning) by the National Sharia Council–Indonesian Ulema Council (DSN-MUI), with specific reference to Fatwa No. 77/DSN-MUI/V/2010 concerning non-cash gold trading. The fatwa has generated scholarly debate, as it permits transactions seemingly contrary to hadiths mandating immediate exchange for ribawi commodities. The study adopts Abdullah Saeed’s contextual hermeneutics, emphasizing implementational values and socio-historical context in interpreting Islamic legal texts. By integrating ethico-legal principles and the objectives of Islamic law (maqasid al-sharia), DSN-MUI engages in a structured hierarchy of values and applies usul al-fiqh methodologies to address contemporary economic challenges. While some critics argue that the fatwa diverges from a strict textualist reading of hadith, the DSN-MUI’s contextual approach demonstrates normative adaptability without compromising sharia principles. This approach responds to emerging financial realities, such as digital transactions, while upholding the public interest (maslahah). The study highlights the significance of hermeneutical methods in balancing the authority of religious texts with the evolving needs of society, and affirms the DSN-MUI’s strategic role in shaping progressive and globally responsive Islamic economic jurisprudence.